Proceedings of the 10th International Conference on Artificial Intelligence and Law 2005
DOI: 10.1145/1165485.1165512
|View full text |Cite
|
Sign up to set email alerts
|

Is linguistic information relevant for the classification of legal texts?

Abstract: Text classification is an important task in the legal domain. In fact, most of the legal information is stored as text in a quite unstructured format and it is important to be able to automatically classify these texts into a predefined set of concepts.Support Vector Machines (SVM), a machine learning algorithm, has shown to be a good classifier for text bases [Joachims, 2002]. In this paper, SVMs are applied to the classification of European Portuguese legal texts -the Portuguese Attorney General's Office Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Other programs have assigned rhetorical roles to case sentences based on manually annotated decisions [24], categorized legal cases by abstract WLN categories (e.g., finance and banking, bankruptcy) [25] or general topics (e.g., exceptional services pension, retirement) [15], and determined the role of a sentence in the case (e.g., as describing the applicable law or the facts) [16].…”
Section: Related Workmentioning
confidence: 99%
“…Other programs have assigned rhetorical roles to case sentences based on manually annotated decisions [24], categorized legal cases by abstract WLN categories (e.g., finance and banking, bankruptcy) [25] or general topics (e.g., exceptional services pension, retirement) [15], and determined the role of a sentence in the case (e.g., as describing the applicable law or the facts) [16].…”
Section: Related Workmentioning
confidence: 99%
“…70-77). More recently, experimenters showed that some linguistic processing, including stemming and part-of-speech tagging helped assign general topic categories (e.g., exceptional services pension, retirement, competence) to legal cases (i.e., decisions of the Portuguese Attorney General's office) (Gonçalves and Quaresma 2005). Both sets of experiments involved automatically assigning abstract topics as categories; in the context of the work reported here, a comparably abstract category would be ''trade secret misappropriation''.…”
Section: Information Extraction From Case Textsmentioning
confidence: 99%
“…- [39] used decision trees to extract rules to estimate the number of days until the final case disposition; - [40] developed rule based and neural networks legal systems; - [7] used neural networks to model legal classifiers; - [14,15] used SVM to classify juridical Portuguese documents; - [34] proposed a framework for the automatic categorisation of case laws; - [30,31] described the use of self-organising maps (SOM) to obtain clusters of legal documents in an information retrieval environment and explored the problem of text classification in the context of the European law; - [23] described classification and clustering approaches to case-based criminal summaries; -[9, 8, 10] described also related work using linear classifiers for documents; - [2] integrated information extraction, information retrieval and machine learning techniques in order to design a case-based retrieval system able to find prior relevant cases. They used SVMs to rank prior case candidates.…”
Section: Related Workmentioning
confidence: 99%